’Plain and Old’: Why Did Paintings Go out of Fashion? - Spliet, Bas (TSEG - The Low Countries Journal of Social and Economic History, 2024)
This article answers a simple question: Who or what pulled the rug from underneath the demand for Dutch paintings in the second half of the seventeenth century? Previous explanations – diminished purchasing power, overproduction, depleted social distinction potential, budget and space constraints – are tested with a unique database of Amsterdam probate inventories but found insufficient. Following scholars like Jan de Vries and Bruno Blondé, I maintain that the downfall of the painting in Dutch interiors is best explained within the framework of the consumer revolution, on which this case study offers a fresh perspective by arguing that the ascent of fashion gave rise to a consumer version of creative destruction. The modernity of Holland’s burgeoning consumer society was borne out of the fact that Dutch burghers simply lost interest.